120k views
5 votes
6 squared = x-7(2x-3)

User Allegria
by
5.1k points

2 Answers

2 votes

Answer: =−13x+21

Step-by-step explanation: Hope this help :D

Let's simplify step-by-step.

x−7(2x−3)

Distribute:

=x+(−7)(2x)+(−7)(−3)

=x+-14x+21

Combine Like Terms:

=x+−14x+21

=(x+−14x)+(21)

=−13x+21

User Victor Santiago
by
5.7k points
3 votes
6^2 = x - 7 ( 2x - 3 )
Factored is : - 15/13
User Axarydax
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.